Revolution and mass democracy : the Paris club movement in 1848 - Amann, Peter H., 1927- (Princeton legacy library., 1975)
Contributing to a growing "history from below" movement, Peter H. Amann argues that the major episodes of the French Revolution of I 848 can be rightly understood only if the perspective of the revolutionaries themselves is taken into account. His history of the Paris club movement of 1848 examines the most significant of the mass organizations through which the tens and perhaps hundreds of thousands of revolutionaries expressed themselves.The author pieces together scattered archival sources to reconstruct the origin, strategies, and main goals of the club movement, and the reasons for its ultimate failure to resist successfully the newly installed republican government's drive to restore traditional authority. He suggests that the club movement may be viewed in a broader, comparative perspective as a characteristic revolutionary phenomenon of a society in transition to modernity.Originally published in 1975.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.